DNA barcoding of Lates calcarifer (Bloch, 1970) - John, Akbar; Kumar, C. Prasanna; Lyla, P.S.; Khan, S. Ajmal; Khan Chowdhury, Ahmed Jalal (Medwell Journals, 2010)
An effort to assess the utility of 650 bp Cytochrome oxidase subunit I (DNA barcode) gene in delineating the members closely resembled marine fin fishes belonging to the family Latidae was made. To address the issue, all 40 barcode sequences of fishes belonging to Latidae family available at NCBI (National Centre for Biotechnological Information) along with the barcode data generated from commonly available fish Asian sea bass (Lates calcarifer) from Parangipettai coastal waters was used. The average GC content of selected three fishes belongs to Latidae was found to be 48.87%. Lates niloticus from Tanzanian waters showed less GC content (47.70%) whereas L. calcarifer from South China sea showed high GC content (49.61%) among the Latidae species studied. Compare to Australian, Indian and Singapore (48.1-48.89%) water L. calcarifer, Myanmar and South China species shows high average GC content (49.38-49.41%). The phylogenetic and genetic distance data showed that the maximum genetic distance is present in 3rd codon position in all the selected species. It is apparent from the genetic distance that the GD between L. calcarifer and L. niloticus was observed to be higher than the GD between P. waigiensis and L. niloticus in all the codon positions. The expected clustering of the species in separate internal branches was well observed in the constructed phylogram with high bootstraps. We conclude that COI sequencing (barcoding) in identifying the morphologically similar species of the family Latidae.